Pengaruh Pemberian Sari Kacang Hijau terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil di PMB Rahayu, S.Tr.Keb., Bdn Lampung Selatan - Ayu Fauziah Aini; Kamidah Kamidah (Jurnal Ventilator, 2024)
The impact of pregnancy anemia will be a risk to fetal development and complications during pregnancy, childbirth, postpartum and can even cause death. The government requires pregnant women to consume Fe tablets but anemia is still not resolved. Apart from consuming Fe tablets, green beans can be used as an effort to increase Hb levels in pregnant women. to determine the effect of giving Green Bean Juice on increasing Hemoglobin levels in pregnant women. Pre-experimental research with a one group pretest posttest research design with a population of all pregnant women, sample 20. Intervention by administering Green Bean Juice at a dose of 100 grams in the morning and evening for 7 days. Analysis test with Paried Sample t-test .average Hemoglobin before treatment was 11.8 gr/dl, while the average hemoglobin after treatment was 12.7 gr/dl, an increase of 0.9 gr/dl. Statistical analysis obtained a p value of 0.000 (<0.005). There is an effect of giving Green Bean Juice on increasing Hemoglobin levels in pregnant women.